Origin and dynamics of a hybrid zone between Ramphocelus tanagers (Thraupidae) in Colombia (2010)
Characterizations of hybrid zones are of importance in evolutionary biology because they can give insights about the characters and processes implied in population divergence. Here, we characterize a hybrid zone between tanagers in the genus Ramphocelus (Thraupidae) located in Western Colombia. We tested whether this hybrid zone originated as a result of secondary contact or of primary differentiation, and described its dynamics across time using molecular, morphological, and plumage coloration data in combination with palaeodistribution modeling. Models of potential historical distributions based on climate data and genetic signatures of population expansion suggest that the hybrid zone originated following secondary contact between two populations that expanded their ranges out of isolated areas in the Quaternary. Concordant patterns of variation in phenotypic characters across the hybrid zone and its narrow extent are suggestive of a tension zone, maintained by a balance between dispersal and selection against hybrids. Comparisons between historical and current specimens suggest the zone has moved towards the east, possibly as a result of sexual selection or of asymmetric gene flow.